Almoner's report for six months, ending 30th June - Mudd, Edith E.
1902-11-19 1902 1900s 4 pages happy and enthusiastic as she was formerly cast down and depressed. This kind of work, therefore, is peculiarly helpful to Hospitals whose Staff must feel that although they are sometimes giving life, they are powerless to give happiness and the means of future subsistence to the permanently crippled. E.E. Mudd 378/IMSW/A/1/4/7a